(3JPcQI GdabgGAs - (3GdMSf (B- (3hjbGd(B: (3GdMSjf (B- (3Hf jhSa GHf Ydj Hf GdeWgQ GdMdj, LeGd GdOjf,J (B726 (3g` s ((3eMeO Hf QajY GdCUagGfi s)
(3ChdgG (B:s
(3bGd ai GdUMGM GdhWhA hbO jbGd GdYbO hgh jOd Ydi ZdHI GSJYeGdg ai GdChd s
(3BNQgG (B:s
(3aGf QLY hgj ai GdYOI agi GeQCJg HGdfcGM GdChd hEf QLY HYO GdYOI hbO JRhLJ adG SHjd YdjgG s
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjIs
(3ef GdfSNI faSgG s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3abg GdePGgH GdCNQis